Effects of Extended-Release Injectable Naltrexone on Self-Injurious Behavior in Rhesus Macaques (Macaca mulatta) - Kempf, Doty J (American Association for Laboratory Animal Science, 2012)
Self-injurious behavior (SIB) is a spontaneous behavior that threatens the health and wellbeing of multiple species. In humans, the opioid antagonist naltrexone hydrochloride has been used successfully to modulate the endogenous opioid system and reduce the occurrence of SIB. This study is the first to assess the efficacy of extended-release naltrexone in the pharmacologic treatment of SIB in rhesus macaques (Macaca mulatta). In an acute pharmacokinetic study of 4 macaques, we determined the mean naltrexone plasma concentration was maintained above the therapeutic level (2 ng/mL) after administration of a single dose (20 mg/kg) of 28-d extended-release naltrexone throughout the release period. For a subsequent treatment study, we selected 8 singly housed macaques known to engage in SIB. The study comprised a 4-wk baseline phase; an 8-wk treatment phase, during which each macaque received 2 doses of extended-release naltrexone 28 d apart; and a 4-wk posttreatment phase. Plasma samples were collected and analyzed weekly for naltrexone concentrations throughout the treatment and posttreatment phases. In addition, total of 6 h of video was analyzed per animal per phase of the study. Compared with baseline phases, both the frequency and the percentage of time spent displaying SIB decreased during the treatment phase, and the percentage of time remained decreased during the posttreatment phase. In contrast, extended-release naltrexone did not alter the expression of other abnormal, anxiety-related, or agonistic behaviors nor were levels of inactivity affected. The present study supports the use of naltrexone in the treatment of SIB in rhesus macaques.